2015
DOI: 10.1007/s11250-015-0860-1
|View full text |Cite
|
Sign up to set email alerts
|

First serological and molecular evidence of PPRV occurrence in Ghardaïa district, center of Algeria

Abstract: In February 2012, an outbreak of peste des petits ruminants (PPR) was suspected in Ghardaïa district at the center of Algeria. Clinical, serological, and molecular investigations were performed to confirm the occurrence of PPRV. The overall morbidity, mortality, and case fatality rates of the ten flocks investigated were 12.2, 2.5, and 20.3 %, respectively. At the flock level, positivity to PPR was 100, 90, and 100 % by competitive ELISA (c-ELISA), RT-PCR of blood samples, and oculo-nasal swabs, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These challenges are typified by the reoccurring outbreaks in the Maghreb region of North Africa (Libya, Tunisia [22, 23], Algeria [24, 25], Morocco [26–28], Mauritania, and the Western Sahara). Mass vaccination following the initial identification of PPRV in Morocco in 2008 resulted in the apparent elimination of PPRV from this country.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges are typified by the reoccurring outbreaks in the Maghreb region of North Africa (Libya, Tunisia [22, 23], Algeria [24, 25], Morocco [26–28], Mauritania, and the Western Sahara). Mass vaccination following the initial identification of PPRV in Morocco in 2008 resulted in the apparent elimination of PPRV from this country.…”
Section: Introductionmentioning
confidence: 99%
“…A year later, Kardjadj et al described the first serological and molecular typing of the PPRV strain implicated in an outbreak in the Ghardaïa district, in the centre of Algeria. The strain clustered under lineage IV of PPRV and shared 97-99% similarity with the strain implicated in neighbouring Morocco and Tunisia (8).…”
Section: The History Of Peste Des Petits Ruminants' Occurrence and DImentioning
confidence: 86%
“…Regular PPRV epizootic activity across the tropical and subtropical areas of North Africa has resulted in the spread of the disease to uninfected areas within the continent (8). The recent results obtained by Kardjadj et al (9) described an overall PPR flock seroprevalence of 42.66% (64/150).…”
Section: The History Of Peste Des Petits Ruminants' Occurrence and DImentioning
confidence: 99%
“…In 2011, PPR was reported in Sahrawi refugee camps in Tindouf district, at the south western border of Algeria with Western Sahara, Mauritania, and Morocco and the sequence analysis clustered the circulating virus under lineage IV of PPRV (De Nardi et al, 2012). A year later, Kardjadj et al (2015a) described the first serological and molecular typing of the PPRV strain implicated in an outbreak in Ghardaïa district, in the center of Algeria. The strain was clustered with lineage IV of PPRV and shared between 97 to 99% similarity with the strain implicated in neighboring Morocco and Tunisia.…”
Section: Molecular Epidemiology Of Ppr In Algeriamentioning
confidence: 99%
“…On the other hand, retrospective surveys on a Moroccan serological bank could not detect PPRV antibodies in small ruminant sera collected before 2008 (Ettair, 2012). The results of the molecular studies in each country show that the lineage IV of PPRV is circulating throughout the sub-region (Abd et al, 2010;De Nardi et al, 2012;Sghaier et al, 2014;Kardjadj et al, 2015a) except Mauritania, where El Arbi et al (2014) reported the presence of the lineage II, therefore, highlighting the existence of a second lineage circulating in North Africa.…”
Section: Molecular Epidemiology Of Ppr In Algeriamentioning
confidence: 99%